2021
DOI: 10.2166/aqua.2021.122
|View full text |Cite
|
Sign up to set email alerts
|

Trophic status, phytoplankton diversity, and water quality at Kafr El-Shinawy drinking-water treatment plant, Damietta

Abstract: This work aims to study the seasonal fluctuation in physicochemical characteristics, trophic status, and some pollutants influencing phytoplankton diversity, and water quality at a compact Kafr El-Shinawy drinking-water treatment plant, Damietta – Egypt seasonally during 2018. Phytoplankton distribution was affected by the trophic status of water, level of pollutants, and physicochemical treatment processes of water. The predominance of phytoplankton species, especially Aphanizomenon flos aquae (Cyanophyta), G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The findings of NW-E DWPFs could be attributed to the sedimentation process that allows suspended particles to settle out [ 32 ]. Similar nitrite trends in which nitrite levels decreased from raw to treated water were also observed in Jiangsu Province, China and Kafr El-Shinawy, Damietta, Egypt [ 31 ]. Overall, the nitrate and nitrite levels measured in NW-E and NW-C DWPFs were within the target water quality range (0–6 mg/L) of [ 23 ] for domestic use.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The findings of NW-E DWPFs could be attributed to the sedimentation process that allows suspended particles to settle out [ 32 ]. Similar nitrite trends in which nitrite levels decreased from raw to treated water were also observed in Jiangsu Province, China and Kafr El-Shinawy, Damietta, Egypt [ 31 ]. Overall, the nitrate and nitrite levels measured in NW-E and NW-C DWPFs were within the target water quality range (0–6 mg/L) of [ 23 ] for domestic use.…”
Section: Discussionsupporting
confidence: 67%
“…This was not the case in the DWPF situated NW-E. Furthermore, in Bayas, Ecuador [ 30 ] and Kafr El-Shinawy, Egypt [ 31 ], phosphate and nitrate levels are always lower in treated water. The latter studies focussed on the water quality of raw and treated water.…”
Section: Discussionmentioning
confidence: 99%
“…(78) Variations in water temperature strongly affect the composition and growth of the phytoplankton community. (79) high turbidity levels reduce light penetration and thus limit phytoplankton growth. (80) Other important factors such as altitude and conductivity are explained in, (81) nitrites and silicates (82) nitrates and total phosphorus (83) and pH (84) in conclusion, diatom research should focus on ecosystem processes and functional characteristics of the assemblages where the fundamental approach would be to link the evaluation of water quality with environmental variables, structure and function of ecosystems, i.e.…”
Section: Variables Ambientales Que Influyentes En La Riqueza De Diato...mentioning
confidence: 99%
“…Summertime is when the amounts of intracellular and extracellular (dissolved) microcystins were highest. Damietta city water had intracellular microcystin levels as 1.70 μg L −1 in summer and 0.71 μg L −1 in winter(Deyab et al 2021).…”
mentioning
confidence: 99%
“…The predominance of phytoplankton species, especially M. aeruginosa (Cyanobacteria), Oscillatoria limnetica (Cyanobacteria), Pediastrum simplex (Chlorophyta), and Melosira granulate (Bacillariophyta) in raw water were documented by El-Adl et al (2020). Furthermore, it was found that the water sources under investigation included both dissolved (extracellular) and cell-bound (intracellular) microbial toxins Deyab et al (2021). reported that season and water treatment had a substantial effect on the levels of intracellular and extracellular microcystin, with water treatment having a greater effect than season.…”
mentioning
confidence: 99%